Active deception defense method based on dynamic camouflage network - Shuo WANG; Jianhua WANG; Qingqi PEI; Guangming TANG; Yang WANG; Xiaohu LIU (Tongxin xuebao)
In view of the problem that the existing honeypots often fail to resist the penetration attack due to the lack of confidentiality,an active deception defense method based on dynamic camouflage network (DCN) was presented.The definition of DCN was given firstly,and then the attacker-defender scenario of active deception based on DCN was described.Next,the interaction process of the attacker-defender scenario was modeled by using a signaling game,whose equilibrium can guide the selection of optimal deception strategy.Furthermore,to quantify the payoffs accurately,the two-layer threat penetration graph (TLTPG) was introduced.Finally,the solution for game equilibrium was designed,through which pure strategy and mixed strategy could be calculated simultaneously.The experimental results show that,based on the dynamic camouflage network,the perfect Bayesian equilibrium can provide effective guidance for the defender to implement the optimal defense strategy and maximize the benefits of the defender.In addition,the characteristics and rules of active deception defense DCN-based are summarized.